AB1244 TUBERCULOUS SPONDYLODISCITIS: A CASE SERIES ANALYSIS. (June 2019) - Ammar, Lobna Ben; Tekaya, Aicha Ben; Mahmoud, Ines; Saidane, Olfa; Hammamia, Mohammed Ben; Tekaya, Rawdha; Abdelmoula, Leila
Abstract : Background: Spinal tuberculosis or Pott's disease is one of the many manifestations of active tuberculosis and is still common in Mediterranean countries such as Tunisia with high endemicity. Definitive diagnosis of tuberculous spondylodiscitis requires the identification of Mycobacterium tuberculosis. Objectives: We aimed to describe clinical, laboratory, diagnostic and therapeutic features of spinal tuberculosis. Methods: Retrospective study including 64 patients followed up in our department between 1999 and 2019. Clinical, biological and radiological data were collected. Therapeutic outcome was studied. Results: We studied 64 patients included 35 women and 17 men with a mean age of 56 years old [16 - 86]. Seven patients had a contact with Mycobacterium Tuberculosis Bacilli and 3 patients had a history of pulmonary tuberculosis. The median delay of consultation was 6 months. Inflammatory back pain was found in 79%. Other clinical symptoms: 27.4% fever, 40.3% night sweats, 74.1% impaired general condition. Neurologic deficiency was noticed in 16.1% of cases. 7 patients had another localization of tuberculosis. The inflammatory biological syndrome was found in 92% of cases. The lumbar spine was involved in 58% of patients, followed by the dorsal spine (41.9%) and cervical spine (9.67%). The spondylitis was multifocal and multi-stage in 24.19% of cases. Plain radiographs revealed narrowing of disc spaces in 67.7% of cases and vertebral erosion, vertebral fracture and a paravertebral spindle in 14.51%. Computed tomography and Spinal magnetic resonance imaging was performed respectively in 62.9% and 70.9% of cases. They showed paravertebral abscess in 66.1%, epiduritis in 56.4%, intra-discal abscess in 3.22%, spinal cord compression in 8.06%, and vertebral ostelysis in 9.67% of cases. Tuberculin Skin Test was performed in 57 (92%) patients and it revealed a positive result in 29 (47%) patients. Disco vertebral biopsy was performed in 45 patients and was contributive in 32.2% of cases revealing caseating granulomas. A four-drug therapy including isoniazid (INH), rifampin (RMP), pyrazinamide (PZA) and ethambutol (EMB) were administered to 59 (95.16%) patients for the initial two months. Three patients received initial three-drug combination therapy. Following the initial 4-drug regimen, most patients continued to receive a two-drug regimen with RMP and INH for a mean duration of nine months. Over 80% of patients had an immobilisation. Adverse effects of anti-TB therapy were noted in 17.7% of the patients; [nausea-vomiting: 1.6%, hepatotoxicity: 9.6%, rash: 3.2%, hyperuricemia: 3.2%]. A surgery was needed for 6.4% of patients. Neurological complication occurred in 4 cases, sepsis occurred in 2 other cases and 2 patients were dead. Conclusion: Spinal tuberculosis results in a significant rate of morbidity due to its insidious course and delayed diagnosis. Early establishment of definitive etiologic diagnosis and appropriate treatment is of paramount importance to prevent development of sequelae. Disclosure of Interests: None declared